Mathematics e-Module with Malay Islamic context for 8th gradestudents: Formative Evaluation on Practicality - Afgani, Muhammad Win; Paradesa, Retni; Khan, Adnan Shahid (Program Studi Pendidikan Matematika, Universitas Islam Negeri Raden Fatah Palembang, 2024)
Study aims to determine the practical of Mathematics E-modules on polyhedron using the context of Malay Islam which contains audio visual packaged attractively using the Canva application and makes it easier for students to understand the material. This research uses quantitative descriptive research methods following the formative evaluation stage in one-to-one, small group and field tests. The subjects of this study were 8th grade students at one of junior high school in Palembang which totaled 31 students. This research resulted in (1) E-modules with